Use of spray-dried sugar cane yeast in pelleted diet or meal diet for piglets in the initial phase - Moreira, Ivan (2008)
A trial was conducted using 144 male and female crossbred piglets (48-to-69-day-old and 15.5kg of initial weight) to evaluate nutritionally and economically sugar cane yeast (Saccharomyces sp.), dried by spray-dryer (SCYSD), in pelleted or meal diet in the piglets feeding. Isolysine, isocalcic and isophosphoric diets were used, based on corn and soybean meal. The experimental design was of randomized blocks, with four treatments in 2x2 factorial scheme, using two SCYSD inclusion levels (7% and 14%) and two physical forms of diets (meal and pelleted) with four replications and nine animals per experimental unit. There were no effects of SCYSD inclusion levels in diets on feed intake, daily weight gain and feed/gain ratio or on cost of feed per kilogram of live weight gain. The pelleted diets provided better daily weight gain, decrease in feed intake, better feed/gain ratio, decrease in diet cost per kilogram of live weight gain and, reduction in daily intake and intake per kilogram of live weight gain of digestible energy, crude protein, lysine and methionine+cystine.